2007
DOI: 10.4064/sm178-3-4
|View full text |Cite
|
Sign up to set email alerts
|

On certain products of Banach algebras with applications to harmonic analysis

Abstract: Abstract. Given Banach algebras A and B with spectrum σ(B) = ∅, and given θ ∈ σ(B), we define a product A × θ B, which is a strongly splitting Banach algebra extension of B by A. We obtain characterizations of bounded approximate identities, spectrum, topological center, minimal idempotents, and study the ideal structure of these products. By assuming B to be a Banach algebra in C 0 (X) whose spectrum can be identified with X, we apply our results to harmonic analysis, and study the question of spectral synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 20 publications
2
38
0
Order By: Relevance
“…Monfared [16] showed that A × θ B is amenable if and only if both A and B are amenable. Moreover, he proved that weak amenability of A and B implies weak amenability of A × θ B, but in general case the converse of this statement is not true.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monfared [16] showed that A × θ B is amenable if and only if both A and B are amenable. Moreover, he proved that weak amenability of A and B implies weak amenability of A × θ B, but in general case the converse of this statement is not true.…”
Section: Introductionmentioning
confidence: 99%
“…The θ-Lau product A × θ B of two Banach algebras A and B, for some nonzero characters θ on B, was introduced and investigated by Monfared [16]. Recently, several notions of amenability were first studied on A × θ B by Monfared [16] and then pursued by Vishki and Khoddami [5] and the authors [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first important paper related to this construction is Lau's paper [16] which he defined a new algebra product on the Cartesian product space A×B for the case where B is the predual of a van Neumann algebra M such that the identity of M is a multiplicative linear functional on B. Later on, Monfared [18] extended the Lau product to arbitrary Banach algebras. This construction has many applications in different contexts, see for examples [9,15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…for all (a, b), (a , b ) ∈ A × θ B. Amenability and weak forms of amenability of A × θ B studied in [5,9]. Let T : B → A be an algebra homomorphism, and A be a commutative Banach algebra.…”
mentioning
confidence: 98%